Thermoresponsive and Injectable Hydrogel for Tissue Agnostic Regeneration. Issue 23 (17th October 2022) - Calder, Dax; Fathi, Ali; Oveissi, Farshad; Maleknia, Simin; Abrams, Terence; Wang, Yiwei; Maitz, Joanneke; Tsai, Kevin Hung‐Yueh; Maitz, Peter; Chrzanowski, Wojtek; Canoy, Ivan; Menon, Vivek Ashoka; et al.
Abstract: Injectable hydrogels can support the body's innate healing capability by providing a temporary matrix for host cell ingrowth and neovascularization. The clinical adoption of current injectable systems remains low due to their cumbersome preparation requirements, device malfunction, product dislodgment during administration, and uncontrolled biological responses at the treatment site. To address these challenges, a fully synthetic and ready‐to‐use injectable biomaterial is engineered that forms an adhesive hydrogel that remains at the administration site regardless of defect anatomy. The product elicits a negligible local inflammatory response and fully resorbs into nontoxic components with minimal impact on internal organs. Preclinical animal studies confirm that the engineered hydrogel upregulates the regeneration of both soft and hard tissues by providing a temporary matrix to support host cell ingrowth and neovascularization. In a pilot clinical trial, the engineered hydrogel is successfully administered to a socket site post tooth extraction and forms adhesive hydrogel that stabilizes blood clot and supports soft and hard tissue regeneration. Accordingly, this injectable hydrogel exhibits high therapeutic potential and can be adopted to address multiple unmet needs in different clinical settings. Abstract : A fully synthetic and ready‐to‐use injectable solution is engineered that forms an adhesive hydrogel in contact with body temperature. The hydrogel provides a temporary matrix for host cell ingrowth and tissue regeneration. Preclinical and clinical results show the potential of the technology to address multiple unmet needs in different clinical settings.